A milestone in the doubled haploid pathway of cassava - Perera, Prasanthi I.P.; Ordoñez, C.A.; Becerra López Lavelle, Luis Augusto; Dedicova, Beata (Springer, 2014)
This study was aimed at inducing androgenesis in cultured anthers of cassava (Manihot esculenta Crantz) to develop a protocol for the production of doubled haploids. Microspore reprogramming was induced in cassava by cold or heat stress of anthers. Since the anthers contain both haploid microspores and diploid somatic cells, it was essential to verify the origin of anther-derived calli. The origin of anther-derived calli was assessed by morphological screening followed by histological analysis and flow cytometry (FCM). Additionally, simple sequence repeat (SSR) and amplified fragmented length polymorphism (AFLP) assays were used for the molecular identification of the microspore-derived calli. The study clearly demonstrated the feasibility of producing microspore-derived calli using heat- or cold-pretreated anthers. Histological studies revealed reprogramming of the developmental pathway of microspores by symmetrical division of the nucleus. Flow cytometry analysis revealed different ploidy level cell types including haploids, which confirmed their origin from the microspores. The SSR and AFLP marker assays independently confirmed the histological and FCM results of a haploid origin of the calli at the DNA level. The presence of multicellular microspores in the in vitro system indicated a switch of developmental program, which constitutes a crucial step in the design of protocols for the regeneration of microspore-derived embryos and plants. This is the first detailed report of calli, embryos, and abnormal shoots originated from the haploid cells in cassava, leading to the development of a protocol for the production of doubled haploid plants in cassava.